Unique photoelectrochemical behavior of TiO2 nanorods wrapped with novel titanium Oxy-Nitride (TiOxNy) nanoparticles. (23rd August 2018) - Arunachalam, Maheswari; Yun, Gun; Ahn, Kwang-Soon; Seo, Won-Seon; Jung, Dae Soo; Kang, Soon Hyung
Abstract: In this work, we developed novel titanium oxynitride (TiOx Ny ) nanoparticles with diameter of 25 ± 2 nm and crystalline size of ∼15 nm on hydrothermally grown one-dimensional (1D) TiO2 nanorod (TNR) arrays. Herein, the TiOx Ny nanoparticles were synthesized by facile nitridation using TiO2 powder at 100% NH3 gas atmosphere. Titanium oxynitride composed of potentially energetic metal-nitrogen bonds (TiN), compared to the weaker TiO bond, becomes chemically stable in the alkaline environment, and is considered as a suitable material for photoelectrochemical (PEC) system. The PEC performance of TiOx Ny decorated TNR (abbreviated as TiOx Ny @TNR) films was evaluated in 0.1 M KOH solution under solar illumination condition, and achieved the potentially high photocurrent density ( J ) of 2.1 mA/cm 2 at 1.23 V versus reversible hydrogen electrode (RHE) (abbreviated as VRHE ) in the TiOx Ny @TNR arrays, in comparison with the poor photoresponse (0.7 mA/cm 2 at 1.23 VRHE ) of the pristine TNR arrays. A nearly three-fold enhancement was attained in the TiOx Ny decorated TNR arrays, attributed to the high visible light absorption and fast carrier separation, due to the hybridization with the visible active TiOx Ny nanoparticles in the cascading band alignment between the TiOx Ny and TNR materials. Furthermore, the introduction of TiOx Ny layer on the TNR surface quite reduces the interfacial resistance in the solid-liquid interface region, and further, the TiOx Ny layer contributes to the passivation of the surface states ( e.g., defect, trap sites etc.) where the charge recombination reaction frequently happens, leading to the improvement of PEC performance. Highlights: Titanium oxynitride (TiOx Ny ) nanoparticles on 1D TiO2 nanorod was well developed. TiOx Ny nanoparticles were synthesized by nitridation using TiO2 powder at 100% NH3 gas. Photocurrent density of 2.1 mA/cm 2 at 1.23 VRHE in the TiOx Ny @TNR arrays was achieved. A three-fold enhancement was attained in the TiOx Ny decorated TNR film versus TNR film.